QbD Enabled Development and Evaluation of Pazopanib Loaded Nanoliposomes for PDAC Treatment - Shinde, Aishwarya; Panchal, Kanan; Patra, Parameswar; Singh, Sonali; Enakolla, Sucharitha; Paliwal, Rishi; Chaurasiya, Akash (AAPS PharmSciTech, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is one of the highly fatal types of cancer with high mortality/incidence. Considering the crucial role of vascular endothelial growth factor (VEGF) in PDAC progression, its inhibition can be a viable strategy for the treatment. Pazopanib, a second-generation VEGF inhibitor, is approved for the treatment of various oncological conditions. However, due to associated limitations like low oral bioavailability (14–39%), high inter/intra-subject variability, stability issues, etc., high doses (800 mg) are required, which further lead to non-specific toxicities and also contribute toward cancer resistance. Thus, to overcome these challenges, pazopanib-loaded PEGylated nanoliposomes were developed and evaluated against pancreatic cancer cell lines. The nanoliposomes were prepared by thin-film hydration method, followed by characterization and stability studies. This QbD-enabled process design successfully led to the development of a suitable pazopanib liposomal formulation with desirable properties. The % entrapment of PZP-loaded non-PEGylated and PEGylated nanoliposomes was found to be 75.2% and 84.9%, respectively, whereas their particle size was found to be 129.7 nm and 182.0 nm, respectively. The developed liposomal formulations exhibited a prolonged release and showed desirable physicochemical properties. Furthermore, these liposomal formulations were also assessed for in vitro cell lines, such as cell cytotoxicity assay and cell uptake. These studies confirm the effectiveness of developed liposomal formulations against pancreatic cancer cell lines. The outcomes of this work provide encouraging results and a way forward to thoroughly investigate its potential for PDAC treatment. Graphical Abstract